2022
DOI: 10.1111/gcb.16275
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence along a climate gradient shapes chemical plasticity of a foundation tree species to both changing climate and herbivore damage

Abstract: Climate change is threatening the persistence of many tree species via independent and interactive effects on abiotic and biotic conditions. In addition, changes in temperature, precipitation, and insect attacks can alter the traits of these trees, disrupting communities and ecosystems. For foundation species such as Populus, phytochemical traits are key mechanisms linking trees with their environment and are likely jointly determined by interactive effects of genetic divergence and variable environments throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 189 publications
(212 reference statements)
0
6
0
Order By: Relevance
“…High‐elevation plants are typically expected to be filtered by abiotic conditions, resulting in increased similarity in their chemistry and other functional traits (Asplund et al, 2022; Bakhtiari et al, 2021). However, climatic spatial heterogeneity typically increases with elevation (Rasmann et al, 2014) which can support specific microhabitat preferences in high‐altitude plants and variation or plasticity in their chemistry (Eisenring et al, 2022; Massatti & Knowles, 2016). Several of the high‐elevation willow species studied here inhabit different microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…High‐elevation plants are typically expected to be filtered by abiotic conditions, resulting in increased similarity in their chemistry and other functional traits (Asplund et al, 2022; Bakhtiari et al, 2021). However, climatic spatial heterogeneity typically increases with elevation (Rasmann et al, 2014) which can support specific microhabitat preferences in high‐altitude plants and variation or plasticity in their chemistry (Eisenring et al, 2022; Massatti & Knowles, 2016). Several of the high‐elevation willow species studied here inhabit different microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…Both the population collection sites and garden locations span an elevation gradient of almost 2000 m, consistent with the species' range and including a difference of 12°C mean annual temperature and >500 mm in mean annual precipitation across source locations and ~350 mm across gardens. These gardens have demonstrated genetic and environmental differences in phenology (Cooper et al, 2019), leaf litter traits (Jeplawy et al, 2021), and phytochemical defense compounds (Eisenring et al, 2022). The benefit of these experimental gardens is enhanced by the inclusion of genomic data based on the identification of >9000 single nucleotide polymorphisms (SNPs) for all genotypes planted across the three gardens.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous community genetics studies have demonstrated significant heritability of herbivore distributions among genotypes of various plant species (Genung et al ., 2012; Tovar‐Sánchez et al ., 2015; Gosney et al ., 2021). Our understanding of these arthropod community and plant genetic interactions has further expanded through research focused on the interplay between environment and plant chemical characteristics, especially in keystone forest trees species belonging to Eucalyptus (Barbour et al ., 2009a,b; Andrew et al ., 2010; Külheim et al ., 2011; Gosney et al ., 2017, 2021) and Populus (Eisenring et al ., 2021, 2022). Many of these same studies have often been limited in their ability to identify specific genes underlying individual arthropod distributions, let alone entire community interactions (Barker et al ., 2019; Wimp et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%